THE IDEOLOGY OF TRUMP ON HIS SPEECH ABOUT JERUSALEM: FAIRCLOUGH'S MODELS OF CDA - Ahmad Faiz; Nurul Chojimah; Ismatul Khasanah (Diglosia : Jurnal Pendidikan, Kebahasaan, dan Kesusastraan Indonesia, 2020)
This research investigates the ideology of Trump on his speech about Jerusalem. This research was aimed to analyze illocutionary acts and the ideology of Trump.. This research used qualitative approach. The design of this research is Critical Discourse Analysis (CDA). This research used Fairclough’s three models of CDA, those are textual analysis, discursive practice and social practice The result that showed that there are five types of illocutionary acts expressed, those are representatives, directives, commissives, expressives and declaratives. Representatives was mostly expressed by Trump. Therefore, the result showed that Trump expressed all types of illocutionary act. The ideology on the speech about Jerusalem showed that Trump intended to use his power to create peace in Jerusalem.